2017
DOI: 10.1038/srep46521
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization of Strength Pareto Multiobjective Optimization with Modified Cuckoo Search Algorithm for Rectangular Array

Abstract: This research proposes the various versions of modified cuckoo search (MCS) metaheuristic algorithm deploying the strength Pareto evolutionary algorithm (SPEA) multiobjective (MO) optimization technique in rectangular array geometry synthesis. Precisely, the MCS algorithm is proposed by incorporating the Roulette wheel selection operator to choose the initial host nests (individuals) that give better results, adaptive inertia weight to control the positions exploration of the potential best host nests (solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Such an optimization will result in the minimization of the Bit Error Rate (BER) for large-scale antenna [55]. In addition, the proposed optimization algorithm could also be run in a more complex antenna array synthesis to optimize locations, excitation amplitudes, and the excitation phase of array elements, achieving a high antenna directivity, small half-power beamwidth, low average side lobe level suppression, and predefined nulls mitigation [56]. Based on the three aforementioned hypotheses, it was observed that the HMSCACSA successfully achieved the fastest convergence, shortest CPU duration, and lowest mean and standard deviation values of fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Such an optimization will result in the minimization of the Bit Error Rate (BER) for large-scale antenna [55]. In addition, the proposed optimization algorithm could also be run in a more complex antenna array synthesis to optimize locations, excitation amplitudes, and the excitation phase of array elements, achieving a high antenna directivity, small half-power beamwidth, low average side lobe level suppression, and predefined nulls mitigation [56]. Based on the three aforementioned hypotheses, it was observed that the HMSCACSA successfully achieved the fastest convergence, shortest CPU duration, and lowest mean and standard deviation values of fitness.…”
Section: Discussionmentioning
confidence: 99%
“…These data represent the initial antibodies, which are the same size as the antigen. In this article, the idea of multi-objective optimization and Pareto genetic algorithm 47,48 are applied, and the process can be expressed as…”
Section: Model Self-learning and Automatic Update Based On Artificial...mentioning
confidence: 99%